O Sistema Internacional de Patentes e a saúde global: as possíveis imbricações no contexto das doenças e populações negligenciadas - Machado, Aritana da Silveira (2021)
The rigidifying of patent standards after the signing of the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS Agreement) within the World Trade Organization caused the economic and technological asymmetries between countries to increase so that guaranteeing access to medicines for certain diseases would become an even greater challenge for developing countries. In order to harmonize domestic laws and institute universal regulation of inventions arising from the intellect the TRIPS Agreement made it possible, through the monopoly right, for pharmaceutical companies to direct their investments in research and development (R&D) of drugs to niche diseases considered profitable. As a result, paradoxically, there was the absence of modern and effective drugs necessary for the treatment of certain diseases and the increase in the price charged for drugs that are essential for the treatment of other diseases, characterizing the incidence of neglected diseases and populations. Thus, diseases such as Leishmaniasis, Hansen's disease, Chagas disease, Sleep disease and Hepatitis C have become part of a group of diseases responsible for high mortality rates annually, especially in less economically favored regions. In view of this, the study aimed to investigate the extent to which the international patent system can be held responsible for the scenario in which neglected diseases and populations are inserted. To achieve the proposed aim, the study was developed based on the systemic-complex theory, using the historical, monocratic and structuralist method of approach and procedure, and the documentary research technique. From the application of the referred methods, it was concluded that like other normative and political instruments articulated at the global level, the current patent regime is part of a package of rules that is at the service of certain actors pursuing interests that do not always approach real global demands. Thus, the responsibility for the lack of access to medicines transcends the normative limits of the patent system, despite being directly intertwined with the epidemiological picture. Nevertheless, some possibilities to mitigate the impact of this regime have been emerging within developing countries and going beyond national borders with a plan to promote access to medicines for the population. These are donations of drugs produced in public and private laboratories and successful negotiations carried out within economic blocks with pharmaceutical companies to purchase cheaper drugs that can serve as a standard for the institution of actions and policies aimed at diseases and neglected populations. Finally, the research is inserted in the Emerging Law of the Global Society concentration area of the Federal University of Santa Maria (UFSM) being linked to the post-graduate program of Sociobiodiversity Rights and Sustainability research.